Management challenges to implementing agile processes in traditional d evelopment organizations - Boehm, B.; Turner, R. (IEEE Software, 2005)
Discussions with traditional developers and managers concerning agile software development practices nearly always contain two somewhat cont radictory ideas. They find that on small, stand-alone projects, agile practices are less burdensome and more in tune with the software indus try's increasing needs for rapid development and coping with continuou s change. Managers face several barriers, real and perceived, when the y try to bring agile approaches into traditional organizations. They c ategorized the barriers either as problems only in terms of scope or s cale, or as significant general issues needing resolution. From these two categories, we've identified three areas - development process con flicts, business process conflicts, and people conflicts - that we bel ieve are the critical challenges to software managers of large organiz ations in bringing agile approaches to bear in their projects.
Keywords: Aerospace engineering; Aerospace materials; Agile methods; Agile software development; Automatic testing; Business processes; Computer industry; DP industry; Programming; Project management; Refining; Software engineering; Software management; Software systems; development process conflicts; process integration; software development management; software industry; systems engineering; traditional development organizations